The Influence of Social Media Marketing on Blind Box Purchase Interest among Generation Z at MINISO Suzuya, Lhokseumawe City - Rizki Aujan Fahri; Sufi Sufi; Nanda Ameliany; Cut Sukmawati; Sutriani Sutriani (Indonesian Journal Economic Review (IJER), 2026)
This study aims to determine the effect of social media marketing on purchase interest in blind box products among Generation Z at MINISO Suzuya, Lhokseumawe City. The study used a quantitative approach with a survey method and a simple linear regression technique. The sample consisted of 100 respondents, determined using the Lemeshow formula (95% confidence level, 10% margin of error) and drawn through non-probability purposive sampling. Data were collected through questionnaires using a five-point Likert scale, direct observation, and documentation, and analyzed with SPSS version 25 after validity, reliability, and classical assumption testing. The results show that social media marketing has a positive and significant effect on blind box purchase interest, indicated by a regression equation of Y = 2.717 + 0.752X, a t-count of 6.782 greater than the t-table of 1.985 with a significance value of 0.000 (p < 0.05), so that the alternative hypothesis is accepted. The correlation coefficient (R) of 0.565 indicates a moderate relationship, and the coefficient of determination (R²) of 0.319 shows that social media marketing explains 31.9% of the variation in purchase interest, while the remaining 68.1% is explained by variables outside this study, such as price, packaging design, word of mouth, and consumer psychological factors. TikTok was the platform most used by respondents (81%) to view blind box promotional content. These findings indicate that social media marketing activity is associated with higher purchase interest in blind box products among Generation Z, and that TikTok is the dominant channel through which respondents accessed such content in this sample.